Improving the stability of methylammonium lead iodide perovskite solar cells by cesium doping - Fan, Yuman; Qin, Helin; Ye, Wang; Liu, Meizhuang; Huang, Feng; Zhong, Dingyong (Thin solid films, 2018)
Organometal halide perovskite solar cells are regarded as a remarkable progress in the field of photovoltaic technology. However, the poor stability of perovskite solar cells becomes a serious issue restricting the commercial applications. Here, we investigate the doping of cesium cations in methylammonium lead iodide perovskite solar cells and the effect on the device stability. Homogeneous doping of cesium into methylammonium lead iodide has been obtained with a concentration up to 15%. For the doped solar cells, an efficiency of 13.2–16.5% has been achieved without significant loss compared with the undoped cells. More importantly, the device stability has been dramatically improved by cesium doping. After staying in a dark atmospheric environment for 7 and 30 days, the unencapsulated devices with 20% cesium doping retained 83% and 60% of the initial efficiency, while the undoped cells remained only 59% and 25% of the initial efficiency, respectively. Density functional theory calculations suggest that the cesium dopants are more positively charged than the methylammonium cations. Meanwhile, the doping of cesium increases the averaged charge of iodines. As a result, the Coulomb interactions between the methylammonium cations and the framework of [PbI6] octahedrons are strengthened, which is considered as an efficient factor to prohibit the diffusion of methylammonium cations and therefore stabilize the perovskite structure. •Up to 15 at.% homogeneous doping of cesium into MAPbI3 has been obtained.•Device stability was dramatically improved by Cs doping without sacrificing PCE.•DFT calculations: Cs dopants are more positively charged than the MA cations.•Cs doping: stronger Coulomb force between MA cations and the PbI6 octahedrons.